Steering Europe: Explaining the Rise of the European Council, 1975–1986. (23rd June 2016) - MOURLON-DRUOL, EMMANUEL
Abstract: This article seeks to explain the emergence of the European Council at the heart of Europe's governance between 1975 and 1986. It highlights four factors that quickly made the newly-created institution both indispensable and stable, despite concerns over the excessive reliance on the intergovernmental method in European cooperation processes. These factors were the rise of globalisation in its multi-faceted policy dimensions, a satisfactory new-found institutional balance, the public impact of societal actors' connections with regular and frequent heads of government meetings and the democratic legitimacy issue in European integration. The article further argues that this period witnessed the de facto emergence of the three-pillar Maastricht structure and shows how the study of the early days of the European Economic Community can shed light on the current development of the European Union and the European Council after the 2009 Lisbon Treaty.